Aplikasi Pengaduan Elektronik Troubleshooting (E-Troubleshooting) Layanan Internet Di Kampus Pnl Berbasis Chatting Mobile - Irnando, Teuku Muhammad Detya; Hidayat, Hari Toha; Husaini, Husaini (Politeknik Negeri Lhokseumawe, 2023)
Wifi or internet plays an important role in student and lecturer facilities. The internet has become a source ofinformation that has been used in many teaching and learning activities and to find references or information in completingassignments given to students. Student activity in using the internet provided by the campus always increases from time to time. The occurrence of internet network disturbances can have an impact on student activities, especially when making assignments or myths using the internet network. UPT computers in charge of providing internet networks are required to be able to meet the needs of students, both in quality and quantity. Internet stability is needed by students in carrying out their activities. Thus the complaint application system is to improve the quality of the internet and make it easier for students to report disturbances or problems from the internet directly to the UPT Computer. The method in this research is Qos and Apriori. The stages of making the application starting from collecting data, making applications and testing. The expected result in this study is to make it easier for students and lecturers to make complaints about internet service disruptions provided by the campus more effectively and practically. The percentage of success rate of the tests that have been carried out on this complaint system reached 90% of the 20 test samples.Keywords— Polytechnic, student, internet service, distraction, android.